EFFECTIVENESS OF PROPOSALS AIMED AT INCREASING THE SECURITY OF FINANCIAL SYSTEMS IN UZBEKISTAN - Rakhmatkhojayev Rashidkhan Rikhstitilla ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Ensuring the security of financial systems in Uzbekistan has become increasingly important in the context of rapid digitalization and the expansion of electronic financial services. The widespread adoption of information technologies in banking, payment systems, and other financial institutions has improved service efficiency and accessibility but has also introduced cybersecurity risks, fraud, and data breaches. This study examines measures implemented to strengthen financial system security, including technological, organizational, and legal interventions, and evaluates their effectiveness in reducing risks and enhancing trust. Key strategies include modernizing information systems, implementing multi-factor authentication, promoting cryptographic protection, training personnel in cybersecurity, and improving regulatory frameworks. The findings emphasize that a comprehensive approach, combining technical, human, and legal measures, is essential for maintaining financial stability, fostering confidence in digital financial services, and supporting sustainable development in Uzbekistan.